15-Lipoxygenase-2 deficiency induces foam cell formation that can be restored by salidroside through the inhibition of arachidonic acid effects - Huang Rong; Yong Xi; Li Tingting; Wen Huling; Zhou Xing; Liao Yichen; You Jun; Yu Chunlei; Xu Peng; Wang Yuquan; Wen Dan; Xia Tianqin; et al. (Open Life Sciences)
15-Lipoxygenase-2 (15-Lox-2) is one of the key enzymes in arachidonic acid (AA) metabolic pathway, which belongs to the unsaturated fatty acid metabolic pathway. This pathway is involved in the foam cell transformation of macrophages during the progression of atherosclerosis (AS). The role of salidroside (SAL) in cardiovascular diseases has been extensively studied, but its impact on macrophage foam cell formation has not yet been clearly clarified. We aimed to determine the effects of 15-Lox-2 deficiency on macrophage (Ana-1 cell) foam cell formation, and those of SAL on 15-Lox-2-deficient macrophages. 15-Lox-2-deficient macrophages were generated using short hairpin RNA. Results indicated that 15-Lox-2 expression in the aorta of atherosclerotic patients is lower than that of the normal group. Additionally, 15-Lox-2 deficiency dramatically promoted macrophage uptake of oxidized low-density lipoprotein (ox-LDL) and increased the Cyclin D1 level while dramatically decreasing caspase3 expression. Furthermore, inflammation, complement, and TNF-α signaling pathways, along with IL1α, IL1β, IL18, and Cx3cl1, were activated in 15-Lox-2-deficient macrophages. These changes were alleviated by SAL through inhibiting AA effects, and the effects of AA on macrophages could be inhibited by SAL. Consistently, phospholipase A2-inhibitor arachidonyl trifluoromethyl ketone (AACOCF3) restored these changes. In summary, SAL reversed the effects of 15-Lox-2 deficiency on macrophages by inhibiting excessive AA and may be a promising therapeutic potential in treating atherosclerosis resulting from 15-Lox-2 deficiency.